Assessment of agrochemical exposure in farmers through urinary residue analysis: a cross-sectional survey - Shabadi, Nayanabai; Basavanagowdappa, H.; T., Rajesh Kumar; Ramesh, Naveen; Narayan, Varshini; S., Chandan R.; Nath, Anchu R. (International Journal Of Community Medicine And Public Health, 2026)
Background: The usage of pesticides has become widespread in agricultural sector to meet the rising demand for food production, especially in developing countries like India. Exposure to pesticides and lack of adequate protective measure leads to various health effects among agricultural workers. The study aims to evaluate pesticide exposure by analysing urine samples from farmers in Mysuru district of Karnataka. Methods: A community-based cross-sectional study was conducted from November 2024 to January 2025 among 100 agricultural workers selected from three primary health centres (PHCs) (Suttur, Hadinaru and Kadakola). Data were gathered through a structured questionnaire, and urine samples were analyzed for the presence of pesticide residues. The statistical analysis involved both descriptive statistics and logistic regression. Results: In the sample of 100 participants, pesticide residues were identified in 21% of the urine samples. Carbendazim and tricyclazole were detected most frequently (7% each). Unsafe practices regarding pesticide handling were prevalent, only 34% reported using personal protective equipment (PPE), and 53% stored pesticides in fields. Although pesticide usage was widespread, the low detection rates might be related to inconsistent exposure. Chronic health issues such as hypertension (14%) and diabetes (12%) were common among participants. Conclusions: The findings show the internal exposure of agrochemicals among farmers and inadequate use of PPE. It is essential to enhance educational outreach, conduct regular health monitoring, and implement regulatory measures to protect the health of farming communities by incorporating occupational health into primary care and enhancing training on safe pesticide usage, PPE, and hygiene.